51. OXIDISED CELLULOSE (SURGICEL) GRANULOMA RADIOLOGICALLY MIMICKING RECURRENT RENAL CELL CARCINOMA: AN EXAMPLE OF IATROGENIC PATHOLOGY DEMONSTRABLE BY HISTOCHEMICAL STAINING. (February 2015) - Sharifi, S.; Burke, P.; Kerr, K.
Abstract : Background: Local haemostatic materials such as oxidised cellulose (Surgicel) are widely used to achieve intraoperative haemostasis. Oxidised cellulose (Surgicel) is typically completely resorbed within weeks of its use. However; a Surgicel granuloma can rarely persist for months to years and can therefore mimic a recurrent neoplasm on imaging studies. Method: We present a case of a 64-year-old man who previously underwent open nephron-sparing surgery for a stage 1a clear cell renal cell carcinoma involving the posterior upper pole of the kidney with negative margins. A post-operative surgical haematoma was noted which was treated conservatively. Twelve months later, imaging studies showed a complex mass immediately anterior to pelvi-uereteric junction in the same kidney. The mass was unable to be dissected from the kidney, and a radical nephrectomy was therefore performed. Results: Macroscopically, a well circumscribed lesion was present within the perinephric fat adjacent to the pelvi-ureteric junction with associated ectasia of the pelvicalyceal system. Microscopically, there was a giant cell granulomatous reaction to scattered islands of a non-refractile weakly eosinophilic foreign material associated with fat necrosis, chronic inflammation and haemosiderin deposition. Histochemical staining for Masson Trichrome stained the foreign material intensely red which was consistent with cellulose matter. No residual clear cell carcinoma was present. Conclusion: Persistent Surgicel granuloma has been previously described in various sites as isolated case reports, all with radiological concern of recurrent neoplasm. Clinicopathological correlation is very useful in such cases. Furthermore, retained Surgicel can be demonstrated with use of histochemical staining (Masson Trichrome). To our knowledge, this characteristic histochemical property of cellulose has not been documented in prior case reports of Surgicel granulomata.